Does obesity impact the outcome of severely burned patients?. Issue 2 (3rd January 2020) - Pauzenberger, Reinhard; Radtke, Christine; Ederer, Ines A.; Hacker, Stefan; Waldmann, Anna; Sternat, Nikolaus; Franke, Isabella; Thury, Alexander; Harpain, Lucie; Stievano, Simona
Abstract: Although obesity appears to be an important predictor of mortality and morbidity, little data about the impact of body mass index (BMI) on the outcome of severely burned patients are available. Patients admitted to the General Hospital Vienna between 1994 and 2014, who underwent surgery because of burn injuries, were enrolled in this study. BMI was used to divide patients into five groups: BMI 18.5 to 24.9, 25 to 29.9, 30 to 34.9, 35 to 39.9, and > 40. The groups were compared in terms of difference of mortality and morbidity. Of 460 patients, 34.3% (n = 158) died. Mortality rates were the lowest in patients with obesity class III and the highest in patients with BMI 35 to 39.9 (BMI 18.5‐24.9: 30.5%, BMI 25‐29.9: 31.5%, BMI 30‐34.9: 41.3%, BMI 35‐39.9: 55.5%, BMI > 40: 30%; P = .031). BMI was not found to be an independent risk factor when corrected with age, percent total body surface area burned, full‐thickness burns, and inhalation injury. No significant differences in length of stay, inhalation trauma, pneumonia, wound infection, sepsis, and invasive ventilation were observed. BMI as an independent risk factor for severely burned patients could not be confirmed via multivariate analysis.